Proper edge colorings of complete graphs without repeated triangles - Botler, Fábio; Colucci, Lucas; Matias, Paulo; Mota, Guilherme; Parente, Roberto; Secco, Matheus (Anais do Encontro de Teoria da Computação (ETC), 2022)
In this paper, we consider the problem of computing the minimum number of colors needed to properly color the edges of a complete graph on $n$ vertices so that there are no pair of vertex-disjoint triangles colored with the same colors. This problem was introduced recently (in a more general context) by Conlon and Tyomkyn, and the corresponding value was known for odd $n$. We compute this number for another infinite set of values of $n$, and discuss some small cases.